Experimental comparison of serpentine and parallel-tubes flat plate collectors for different flow rates - Plaza-Gomáriz, Francisco de Asís; Cejudo-López, José Manuel (My University, 2019)
Comparación experimental del comportamiento térmico de dos captadores solares térmicos, uno serpentín y otro parrilla. In the paper, two flat plate solar collectors were simultaneously tested in a side-by-side facility at the UMA, following the steady-state procedure proposed by the EN12975-2:2006 standard. Both collectors have been manufactured at the same date by the same company and belong to the same product range. To demonstrate the relationship between the thermal performance of each collector and the mass flow rate, both collectors were tested for a total of seven flows, which covered all the technically possible flows in a real SDHW installation. Next, the measurement uncertainties were propagated and the different performance curves for each test were obtained, which allowed to have the three characteristic curve coefficients that are usually used to compare different collectors in terms of their operation (collector efficiency and linear and quadratic heat losses coefficients). The paper analyses the suitability of each type of absorber plate configuration and the influence of the mass flow rate. The paper recommends a type of collector depending on their working conditions.
Keywords: Termodinámica -- Congresos; Congresos y conferencias; Colector solar plano; Solar térmica; Serpentin vs Parrilla; Caudal variable